2021
DOI: 10.1002/joc.7461
|View full text |Cite
|
Sign up to set email alerts
|

A novel selection method of CMIP6 GCMs for robust climate projection

Abstract: The selection of global climate models (GCMs) is a major challenge for reliable projection of climate. A novel method is introduced in this study to select couple model intercomparison project phase 6 (CMIP6) GCMs. Climatology maps of GCM simulated precipitation, maximum temperature and minimum temperature data were rasterized to form 8‐bit grey scale images, which were subsequently merged to form a colour image. The GCMs' climatology images were compared with the climatology image prepared using gridded clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 56 publications
1
20
0
1
Order By: Relevance
“…All models were developed using CIT, VCCT, and XFEM. Based on the results deduced from the T6 simulations, the most suitable technique was determined by using five different statistical indicators that are used by researchers in different fields [ 37 , 38 , 39 ]. These statistical indicators are: 1. root mean square error (RMSE); 2.…”
Section: Fe Models Verification and Discussionmentioning
confidence: 99%
“…All models were developed using CIT, VCCT, and XFEM. Based on the results deduced from the T6 simulations, the most suitable technique was determined by using five different statistical indicators that are used by researchers in different fields [ 37 , 38 , 39 ]. These statistical indicators are: 1. root mean square error (RMSE); 2.…”
Section: Fe Models Verification and Discussionmentioning
confidence: 99%
“…It has mild cold winters and hot summers, and rainfall is rare. The annual rainfall is about 200 mmÁyear −1 in the northern parts and less than 5 mmÁyear −1 in the far south (Nashwan et al, 2020;Yassen et al, 2020;Hamed et al, 2021a;2021b). Due to the shortage of water, most Egyptians live along the Nile in nearly 4% of Egypt's total land.…”
Section: Study Areamentioning
confidence: 99%
“…GCMs are commonly used for projecting temperature and precipitation change (Her et al ., 2019). Thus a number of studies reported using ensemble of more appropriate GCMs by excluding those considered unrealistic; doing so can reduce uncertainties in mean changes in projected precipitation and temperature (Khan et al ., 2020; Nashwan and Shahid, 2020; Hamed et al ., 2022b). Besides, GCM subsetting can address the issue of resource limitations by handling many GCMs for climate change assessment (Salman et al ., 2018; Salehie et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%